PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF DESKRIPSI SISWA SEKOLAH DASAR PEKANBARU - Siti Amaliyah; Zariul Antosa (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2018)
This research is based on the low skill of writing a paragraph. Description of third-grade students of primary school, from 22 students, only 8 students (40%) are skilled and the remaining 12 students (60%) are less skilled. This research is an Action Research conducted in 2 cycles per cycle consisting of 2 meetings. This study aims to improve the skills of writing description paragraphs with the use of image media. The subject of this research is the third-grade students of primary school in Pekanbaru. Data obtained through observation and test. The data analysis technique used is descriptive statistical technique. The results showed that the percentage of teacher activity scores on the first cycle of 66.66%, while in cycle II the percentage score of 91.66%. Student activity in learning also experience improvement, student activity on cycle I score percentage equal to 6.66% whereas in cycle II percentage score equal to 91.66%. The results of the writing skill of the descriptive paragraph on an average baseline score of 65.3. Meanwhile, the value of the writing skill of the descriptive paragraph in the first cycle score average score of 87.2, then cycle II increased with an average of 89. It can be concluded that using image media can improve the skills to write paragraphs description of primary students.